Przyszłość już była. Dystopie w najnowszym kinie science fiction Ameryki Łacińskiej - Racięski, Bolesław (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
This paper examines the various ways in which contemporary Latin American science fiction films contest the neocolonial and neoliberal narratives, dominant in the region since the 20th century. I identify and examine strategies that filmmakers employ to challenge the common understanding of such notions as time, modernity and technological progress. I outline the visions of dystopias presented in the examined films, while also analyzing the counter-narratives introduced by filmmakers, which are mostly focused on creating a new, hybrid identity for a future citizen.